Development of Virtual Manufacturing Architecture Using Wearable Sensor, Image Processing and 3D CAD System - Kiswanto, Gandjar; Ayu Setiani, Adjeng; Rakhmat Ramadhan, Dody; Zhultriza, Ferdiansyah; Fathin Juzar, Muhammad; Muhammad Suryantoro, Rachmad (International Journal of Engineering and Technology, 2018)
This research aims to develop an architecture that can read the movement and contraction of human arm muscles to allow human interact with virtual objects in a novel way. Experiments were conducted to allow users to have both kinesthetic and visual interaction with virtual objects by combining biofeedback from electromyogram (EMG), kinesthetic and visual information from hand image processing. From the results of the research, this model architecture allows virtual objects to be grasped, moved and dropped through muscle exertion classification based on physical world masses.